2021
DOI: 10.1186/s13148-021-01197-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications in thymic epithelial cells: an evolutionary perspective for thymus atrophy

Abstract: Background The thymic microenvironment is mainly comprised of thymic epithelial cells, the cytokines, exosomes, surface molecules, and hormones from the cells, and plays a vital role in the development, differentiation, maturation and homeostasis of T lymphocytes. However, the thymus begins to degenerate as early as the second year of life and continues through aging in human beings, leading to a decreased output of naïve T cells, the limited TCR diversity and an expansion of monoclonal memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 154 publications
0
1
0
Order By: Relevance
“…Being the major lymphoid organ, the thymus is a pertinent site for the development, differentiation, and maturation of T lymphocytes [ 89 ]. The spleen is the largest secondary lymphoid organ in the body, where several T and B lymphocytes settle down and participate in various immune functions [ 90 , 91 ]. Wu [ 92 ] et al documented that traditional Chinese medicine increased the activities of acid phosphatase (ACP) and lactate dehydrogenase (LDH) in the spleen of immunocompromised mice.…”
Section: Discussionmentioning
confidence: 99%
“…Being the major lymphoid organ, the thymus is a pertinent site for the development, differentiation, and maturation of T lymphocytes [ 89 ]. The spleen is the largest secondary lymphoid organ in the body, where several T and B lymphocytes settle down and participate in various immune functions [ 90 , 91 ]. Wu [ 92 ] et al documented that traditional Chinese medicine increased the activities of acid phosphatase (ACP) and lactate dehydrogenase (LDH) in the spleen of immunocompromised mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our investigation revealed significant epigenetic changes in both mouse and human TECs during aging, which can impact various aspects of TEC function and senescence. Previous studies have demonstrated the influence of epigenetic changes on the expression of Foxn1, the epithelial-to-mesenchymal transition of TECs to adipocytes, and the expression of tissue-restricted self-Ags ( 39 40 ). Moreover, our analysis also highlighted potential involvement of other unstudied epigenetic factors, such as histone methylation, histone acetylation, and DNA methylation, which may contribute to age-related TEC dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Acute thymic involution may also take place. It is induced by different microbes, glucocorticoids, radiation, or use of chemotherapy and is associated with development of inflammation [21]. It has been demonstrated that premature thymus atrophy is at least partially caused by the damage of stromal cells by oxidative stress, associated with the deficiency of catalase, an important enzyme-antioxidant catalyzing reaction in which hydrogen peroxide turns into water and oxygen [22].…”
Section: Thymus Involutionmentioning
confidence: 99%
“…Neither of them can be rejected, just as neither can be accepted without hesitation. First is that cells of the perivascular space, such as mesenchymal stem cells, perivascular cells, and pericytes, differentiate into adipocytes through the activation of peroxisome proliferator-activated receptors (PPARγ), the main adipogenic transcription factor [21].…”
Section: Thymus Involutionmentioning
confidence: 99%